CONCEPTUAL APPROACHES TO THE CHANGE MANAGEMENT IN FOREIGN STUDIES - E. Shironina (Publishing House of the State University of Management, 2019)
A systematized overview of change management conceptual approaches, presented in foreign studies, has been adduced. Fundamental assumptions, underlying each approach, have been shown. Advantages and limitations of change management approaches have been considered. Systematization of conceptual approaches to change management in three dimensions has been proposed: “business orientation” (biological, rational, resource, systems, contingency perspective approaches), “power orientation” (institutional, political approaches) and “people orientation” (psychological, cultural approaches). It has been shown, that postmodern conceptual approach is an attempt to build an intelligent object (process of change) in all three dimensions.